The Associations Between Functional Mobility, Dynamic Stability and Back Pain in Women After Caesarean Section Surgery - Laura Žalienė; Irina Arup (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Lower back pain is more common in women who have undergone cesarean section surgery than in women whose childbirth was natural. The quality of life is better, and the level of disability is lower in women who have given birth naturally than those who have undergone cesarean section surgery.